Juridical Analysis of the Prohibition of Political Campaigns in Places of Worship According to the Constitutional Court Decision No. 65/PUU-XXI/2023 in the Perspective of Maslahah Mursalah - Martabela, Pepni; Burlian, Paisol; Harun, Muhamad (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study discusses the prohibition of political campaigns in places of worship as regulated in Article 280 paragraph (1) letter h of Law Number 7 of 2017 on General Elections, which became the subject of review in the Constitutional Court Decision No. 65/PUU-XXI/2023. The research focuses on the Constitutional Court’s legal considerations and provides a juridical analysis of the decision through the perspective of Maslahah Mursalah. Using a normative legal approach, the study examines statutory documents and legal theories developed by Jimly Asshiddiqie, Djokosoetono, Gustav Radbruch, and Abdul Wahab Khallaf. The findings indicate that the decision arose due to legal uncertainty between the article’s norm and its explanatory note. The Court ruled that the explanation of Article 280 paragraph (1) letter h contradicts the 1945 Constitution and has no binding legal force. From the Maslahah Mursalah perspective, campaigning in places of worship may be permissible if it upholds sanctity, order, and respect for religious practices, aligning with the principle of public benefit and Islamic legal justice. [Penelitian ini membahas larangan kampanye di tempat ibadah sebagaimana diatur dalam Pasal 280 ayat (1) huruf h Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum, yang menjadi objek pengujian dalam Putusan Mahkamah Konstitusi Nomor 65/PUU-XXI/2023. Fokus kajian ini meliputi pertimbangan hukum Mahkamah Konstitusi serta analisis yuridis terhadap putusan tersebut dalam perspektif Maslahah Mursalah. Penelitian ini menggunakan pendekatan hukum normatif dengan menelaah dokumen perundang-undangan serta teori hukum dari Jimly Asshiddiqie, Djokosoetono, Gustav Radbruch, dan Abdul Wahab Khallaf. Hasil penelitian menunjukkan bahwa lahirnya putusan ini didorong oleh adanya ketidakpastian hukum antara norma dan penjelasan pasal. Mahkamah menegaskan bahwa penjelasan Pasal 280 ayat (1) huruf h bertentangan dengan UUD 1945 dan tidak memiliki kekuatan hukum mengikat. Dalam perspektif Maslahah Mursalah, kampanye di tempat ibadah dapat diperbolehkan apabila dilakukan dengan menjaga kesucian, ketertiban, dan tidak mengganggu pelaksanaan ibadah. Hal ini sejalan dengan prinsip kemaslahatan umat dan keadilan sosial yang menjadi dasar pembentukan hukum Islam.]